BIOSISTEMATIK SPECIES Annona muricata, Annona squamosa DAN Annona reticulata DENGAN PENDEKATAN ALKALOID - Hamidah; Santoso; Rina Kasiamdari (The East Java Biological Society, 2012)
This research aimed to explore kinship Annona muricata, Annona squamosa and Annona reticulata on the basis alkaloid content. Study phenotype Annona muricata, Annona squamosa and Annona reticulata based alkaloid content. Data alkaloid obtained are then processed by a computer program SPSS version 14. The results of this study indicate that the presence of variations in the character of the three types of Annona of species alkaloid. From the data analysis it can be seen that there are differences in the variations that occur in Annona muricata, Annona squamosa and Annona reticulata by different habitats and is a variation of phenotypic variation. Dendrogram grouping results suggest that Annona squamosa and Annona reticulata fenetic ties closer, so clumped into one large group while Annona muricata Annona split away from the other groups.